Studies of Interaction Mechanism Between Iron and HCN - Tan, Houzhang; Wang, Xuebin; Niu, Yangqing; Liu, Haiyu; Wang, Congling; Xu, Tongmo (Asian Journal of Chemistry, 2010)
Interaction mechanism between iron and HCN has been investigated in a fixed bed, compared with calcium and magnesium and the original HCN is generated by pyridine pyrolysis. Results show that the interaction mechanism of HCN with Fe2O3 is totally different from CaO and MgO. Ferric oxide can transform HCN into NO, compared with that CaO and MgO convert HCN to N2. Under the effect of Fe2O3, HCN begins to decrease at 473 K and when temperature is higher than 623 K, all HCN has been transformed. CH4 starts to decrease linearly at around 348 K, disappearing at 623 K and CO increases continually from 348 K. The reaction between HCN and Fe2O3 is suggested as 2Fe2O3 + 3HCN → 2Fe + 3CO + 3NO + 0.5H2. Iron formed in the reaction of HCNFe2O3 can further react with HCN to transform the nitrogen in HCN into N2. Iron starts to reduce HCN from 423 K, when temperature is higher than 598 K, HCN has been converted completely and the nitrogen elements of N2 are balanced with that of inlet HCN.